허혈성 뇌손상 백서에서 加減聰明湯이 인지기능에 미치는 효과 - 김경윤(Kyung Yoon Kim); 김형우(Hyung Woo Kim); 이상영(Sang Yeong Lee); 차대연(Dae Yeon Cha); 이석진(Seok Jin Lee); 김계엽(Gye Yep Kim); 김행중(Hang Jung Kim); 정현우(Hyun Woo Jeong) (동의생리병리학회지, 2008)
ChongMyeong-Tang (CMT) have been used clinically to treat patient with amnesia and dementia. In addition, CMT have been also used for examinee to improve learning ability in Korea. This study was designed to investigate the effects of Gagam-ChongMeong-Tang (GCMT) on cognitive dysfunction recovery after ischemic brain injury in rats. Rats were divided into three groups; (1) normal, (2) commercial diet after ischemic brain injury (control), (3) CMT diet after ischemic brain injury (experiment). In our study, we carried out Morris water maze test for cognitive motor behavior test and immunohistochemistry study through the change BDNF in the hippocampus(7th, 14th day). In Morris water maze test, cognitive motor function recovery was significantly increased in the experiment group as compared with control group on 7th and 14th day (p<0.01). In immunohistochemistric response of BDNF in the hippocampus, more immune reaction was investigated in the experiment group as compared with control group on 7th and 14th day. Especially more immune reaction was experimented 14th day. These results imply that GCMT can play a role in facilitating recovery of cognitive function after ischemic brain injury in rats. KCI Citation Count: 3